If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 + 6u = 4u + 24 Reorder the terms: 43 + 6u = 24 + 4u Solving 43 + 6u = 24 + 4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-4u' to each side of the equation. 43 + 6u + -4u = 24 + 4u + -4u Combine like terms: 6u + -4u = 2u 43 + 2u = 24 + 4u + -4u Combine like terms: 4u + -4u = 0 43 + 2u = 24 + 0 43 + 2u = 24 Add '-43' to each side of the equation. 43 + -43 + 2u = 24 + -43 Combine like terms: 43 + -43 = 0 0 + 2u = 24 + -43 2u = 24 + -43 Combine like terms: 24 + -43 = -19 2u = -19 Divide each side by '2'. u = -9.5 Simplifying u = -9.5
| 3(-28-7x)=42 | | 14x^2+6x=0 | | -4(w-u)+2(6u+6w)= | | 47+6b=12b+65 | | 66=4x-20 | | -9(v+5)=-3v-3 | | 12-(x+2)=4x | | (4)x+3=29 | | 3x=5x-12 | | 0.6x=100 | | 11-9x+40=6x | | 0.83x=12 | | 3x+11=5x-25 | | 2*12+2w=34 | | 24-5n=-6 | | 105+10x=25x | | -(-5y+w)+4(5w+y)= | | 3x+y-2z=-3 | | x^2-0x+9=0 | | 2x+5+5x=180 | | 0.75p+4=7 | | 4x^2-0x+9=0 | | 7+6x=55 | | 10y^6+15y^5-25y^4=0 | | 6(x-2)=2x+4 | | 12(x^2+2)-48x^2=0 | | 1.50r+13=35.50 | | (4g-3)-(2g+7)=6-g | | 2x+66=5y | | -y^2+10y+x-25=0 | | 4f-7(2f+2)=2f+10 | | 3.3x-2=2.3x |